ORTHOPHRAGMINIDS FORAMINIFERAL ASSEMBLAGES FROM AN ILERDIAN-EARLY CUISIAN REFERENCE SECTION (SAKARYA SECTION, HAYMANA-POLATLI BASIN, CENTRAL ANATOLIA-TURKEY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The Sakarya section represents a highly fossiliferous part of the Haymana-Polatli basin succession (central Anatolia), consisting of mainly nummulitid, alveolinid and orthophragminid foraminifera.  This section, formerly proposed to serve as a reference section for early Ilerdian-early Cuisian Shalow Benthic Zones in Turkey by the "Early Paleogene working group", was studied for its orthophragminid foraminifera, and a sequence of populations has been subjected to biometric analysis of the embryo and equatorial chamberlets.  Discocyclina, which occurs throughout the section, is mainly represented by primitive specimens of Discocyclina archiaci; D. archiaci bakhchisaraiensis and Discocyclina sp. 1 in the lowermost part, which is regarded as of middle Ilerdian age (orthophragminid zone 3).  Upwards, different developmental stages of D. archiaci; transitional developmental stages of D. archiaci bakhchisaraiensis-staroseliensis and D. archiaci staroseliensis are accompanied sporadically by unribbed Orbitoclypeus, O. schopeni suvlukayensis and Discocyclina sp. 1.  This part of the section is regarded as middle-late Ilerdian in age (orthophragminid zone 4).  A more diverse assemblage, represented by Nemkovella, Asterocyclina, ribbed and unribbed Orbitoclypeus accompanied by different Discocyclina species occurs in the uppermost part, which is thought to represent the transitional late Ilerdian-early Cuisian orthophragminid zones (orthophragminid zone 4/5).  In these horizons, N. strophiolata fermonti, N. evae, primitive developmental stages of D. augustae sourbetensis, O. douvillei douvillei, D. fortisi fortisi, A. stella and O. munieri munieri are accompanied by D. archiaci staroseliensis, transitional developmental stages of D. archiaci staroseliensis-archiaci, O. schopeni suvlukayensis and Discocyclina sp. 2.  Biometric data allow refinements with respect to the stratigraphic ranges of some discocyclinid and orbitoclypeid foraminifera. This paper records the first description of orthophragminids from the middle-late Ilerdian/early Cuisian marine deposits of Turkey.